2022
DOI: 10.1590/1519-6984.256277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indole-3-Butyric Acid (IBA) and rooting media on rooting and survival of air layered wax apple (Syzygium samarangense) CV Jambu Madu

Abstract: The wax apple or jambu madu, is a non-climacteric tropical fruit from Myrtaceae family and widely cultivated in South East Asia. The limited availability of good quality seedlings of wax apple is the main problem to development of flourish it’s market share in the current fruit industry. Therefore, in order to produce good quality planting materials, a study aimed at optimizing propagation and adventitious rooting technique and survivability of wax apple air layer was conducted. In this study, four different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Stimulation of cell division and cell elongation at shoot apex together with an improvement in photosynthetic efficiency is due to the increase activity of exogenously treatment with IBA which finally resulted increased in plant height, leaves length and number of leaves reported in carrot . Increased in number of leaves, leaves length and plant height due to IBA was also observed in apple (Malus pumila) cuttings (Khandaker et al, 2022). Increased in number of leaves, leaves length and plant height due to IBA was also observed in apple (Malus pumila) cuttings (Khandaker et al, 2022).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Stimulation of cell division and cell elongation at shoot apex together with an improvement in photosynthetic efficiency is due to the increase activity of exogenously treatment with IBA which finally resulted increased in plant height, leaves length and number of leaves reported in carrot . Increased in number of leaves, leaves length and plant height due to IBA was also observed in apple (Malus pumila) cuttings (Khandaker et al, 2022). Increased in number of leaves, leaves length and plant height due to IBA was also observed in apple (Malus pumila) cuttings (Khandaker et al, 2022).…”
Section: Resultsmentioning
confidence: 81%
“…Increased in number of leaves, leaves length and plant height due to IBA was also observed in apple (Malus pumila) cuttings (Khandaker et al, 2022). Increased in number of leaves, leaves length and plant height due to IBA was also observed in apple (Malus pumila) cuttings (Khandaker et al, 2022). Floral traits were also positively affected by IBA concentration.…”
Section: Resultsmentioning
confidence: 83%
“…A perfect example is the IBA discussed in this study. As a slightly water-soluble substance (200 mg L –1 ), IBA cannot be used at higher concentrations without adding a co-solvent to enhance solubility. However, to avoid the addition of alcohol or other adjuvants, it was shown in earlier studies that transforming IBA into ammonium salts or binary mixtures contributed to the improvement of this parameter. , For the DILs 1–3 obtained as well, the improvement in solubility of IBA in ionic form was noticed. From the solubility analysis, one can be observed that DILs 1–3 were dissolved at 22, 25, and 20 g L –1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The difficulty of rooting was also associated with callus formation. Babashpour et al [26] found no difference in rooting success independent of the concentration of exogenously applied IBA in semi-hardwood cuttings of Bougainvillaea sp., while Camellia et al [27] and Khandakera et al [28] reported that rooting success improved with increasing IBA concentration in Syzygium samarangense and Jatropha curcas [27,28]. To stimulate better rooting of mature stock material, a higher auxin concentration could be used (>5000 ppm) or the auxin used (IBA) could be replaced by another auxin, which is also often used exogenously to improve rooting, such as 1-naphthaleneacetic acid (NAA) or IAA.…”
Section: Discussionmentioning
confidence: 99%